Effect of Cognitive Intervention on Children with ADHD. (1st February 2015) - Gharebaghy, Soraya; Rassafiani, Mehdi; Cameron, Debra
ABSTRACT Although not considered a diagnostic criterion in DSM-IV, motor difficulties in children with Attention Deficit Hyperactivity Disorder (ADHD) are commonly reported. Prevalence of co-morbidity of ADHD and Developmental Coordination Disorder is as high as 50%. Cognitive Orientation to daily Occupational Performance (CO-OP) is a problem-solving approach originally developed for children with Developmental Coordination Disorder. In this approach, therapists support children to use cognitive strategies in a process of guided discovery to solve occupational performance problems. A single case experimental design (multiple baselines) was used to examine the influence of a 12-week intervention using CO-OP with six children with ADHD. Outcome measures included the Canadian Occupational Performance Measure (COPM), Goal Attainment Scaling and the Bruininks–Oseretsky Test of Motor Proficiency and Performance (BOTMP). The results of this study demonstrated improvements in both goals and motor performance in the participants due to the intervention. These results provide some support for the use of CO-OP with children with ADHD. Further research into the application of CO-OP with children with ADHD is warranted based on these preliminary positive findings regarding the efficacy of this intervention to address motor-based performance difficulties.